A guide for ensuring inclusion and equity in education - UNESCO (UNESCO, 2017)
With this Guide, UNESCO seeks to offer practical support to Member States to review how well equity and inclusion currently figure in existing policies, decide what actions need to be taken to improve policies, and monitor progress as actions are taken. An assessment framework is proposed to accompany countries in this review exercise, by taking into account four key dimensions: concepts, policy statements, structures and systems, and practices.